CICLESONIDE IN TREATMENT OF CHILDHOOD BRONCHIAL ASTHMA - K. E. Efendieva; L. S. Namazova-Baranova; Yu. G. Levina; E. A. Vishneva; A. A. Alekseeva; E. G. Bokuchava (Вопросы современной педиатрии)
The review of clinical trials, confirming high efficacy and safety of new inhalation glucocorticoid based on ciclesonide in treatment of childhood bronchial asthma is shown in this article. Ciclesonide is an extra-fine dispersed glucocorticoid with high pulmonary bioavailability (52%), 55% of it is distributed through peripheral respiratory tract, which plays significant role in development and clinical course of asthma. High anti-inflammatory activity, minimal systemic and local side effects and one-time administration per day make this drug usage preferable in pediatric practice.